2019
DOI: 10.1002/ccr3.2617
|View full text |Cite
|
Sign up to set email alerts
|

Case report of patient experience influenced by inadequate interactions between primary, secondary, and tertiary healthcare services in the south of Saudi Arabia

Abstract: This report explains how health system failure can hinder provision of healthcare for a common health problem. Inadequate healthcare delivery can create barriers, lead to stress, prolong waiting time, and affect overall well‐being of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…The region is served with 20 Hospitals employing 1,505 physicians serve the region, and 3,753 nurses (Ministry of Health Saudi Arabia, 2016). As a developing nation, the KSA has a healthcare system that comprises primary, secondary and tertiary hospitals (Gosadi, 2020). The 20 general hospitals comprise 17 secondary, two tertiary and one mental health hospital.…”
Section: Materials and Me Thodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The region is served with 20 Hospitals employing 1,505 physicians serve the region, and 3,753 nurses (Ministry of Health Saudi Arabia, 2016). As a developing nation, the KSA has a healthcare system that comprises primary, secondary and tertiary hospitals (Gosadi, 2020). The 20 general hospitals comprise 17 secondary, two tertiary and one mental health hospital.…”
Section: Materials and Me Thodsmentioning
confidence: 99%
“…However, in developing countries, the occurrence rate of these injuries remains high due to a lack of safe injection training and procedures and a lack of awareness on blood-borne illnesses (Chowdhury et al, 2011;Gosadi, 2020;Pandit & Choudhary, 2008). Among HCW, nurses are exposed to many sharps and a high risk of blood-borne infectious diseases.…”
mentioning
confidence: 99%
“…This continued growth has led to healthcare challenges such as increased population, resulting in high health care costs. Jazan is considered one of the regions with the lowest healthcare quality in the country [ 18 ].
Fig.
…”
Section: Introductionmentioning
confidence: 99%
“…Informative sessions for medical personnel on basic oral health problems can help physicians to make appropriate referrals [61], which should be a feature of oral health care in Saudi Arabia. A study found that the health system in Jazan has an inadequate referral system for delivering high-quality health services [12]. However, adopting a referral system in Jazan can make dental care less costly and help the public to access effective oral care solutions.…”
Section: Discussionmentioning
confidence: 99%
“…Based on a 2019 survey on patient’s satisfaction with the Saudi Ministry of Health (MOH) services, about 72.2% of the patients indicated their satisfaction. However, the Jazan region scored the lowest patient satisfaction compared to other regions [12]. Also, Jazan recorded a high prevalence of dental caries because of inadequate oral-hygiene practices, high consumption of soft drinks, and high sugar consumption, which is considered to be widespread in Saudi Arabia [13].…”
Section: Introductionmentioning
confidence: 99%